(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
In the last decade, radical behaviorists have been studying private events. Skinner overtly admits the occurrence of covert links in behavioral complex events, as it is the case of the problem solving behavior, but presents no explicit procedure to study covert behavior. In order to understand problem solving behavior it is necessary to focus on subject’s flow of the responses in their attempts to reach the solution. Therefore we must find procedures to explicit covert behaviors which occur while one solves a problem. Whichever they may be, they must rely on subject’s (spoken or written) verbal behavior which has to be analyzed and interpreted. This work proposes a procedure for classifying the subject’s verbal behavior emitted during a task of problem solving. It also discusses methodological decisions and implications for the study of private events.